TINJAUAN LITERATUR MANAJEMEN BERPUASA RAMADHAN BAGI PENDERITA DIABETES MELITUS TIPE 2 - Ayu Dinda Fatimah (JUMANTIK (Jurnal Ilmiah Penelitian Kesehatan), 2019)
One of the main causes of death in Indonesia is non-communicable diseases. One of the most common non-communicable disease is diabetes mellitus. Type 2 diabetes mellitus is a category of diabetes that most people in the world suffer from. Diabetes mellitus is a chronic disease characterized by high levels of blood glucose which can lead a number of symptoms and complications if there is no regular monitoring of blood glucose levels and not paying attention to things that can affect blood glucose levels. Things that can affect blood glucose levels are adequate nutritional intake and physical activity.Indonesia is a religious country because it recognizes 6 religions. Indonesia is also a country with the largest Muslim population in the world. One of the activities carried out continuously every year by a Muslim is fasting during the month of Ramadan. Fasting is one form of spiritual awareness that has many benefits, such as, heightening consciousness of God, adopting healthier lifestyle, loving and charity, increasing community spirit, and raising people to become a better version of themselves.However, people with type 2 diabetes mellitus have to know that changes in nutritional intake and physical activity can affect their bodies. Therefore, people with diabetes mellitus have to know the management of diabetes mellitus during Ramadan fasting and they have to do self-management properly to avoid complications that can occur, such as hypoglycemia, hyperglycemia, diabetic ketoacidosis, dehydration, and thrombosis. Keyword: Diabetes Mellitus Type 2, Spiritual Awareness, Self-management, Ramadan Fasting, Glucose Blood Level, Complication